SARS-CoV-2 surface and air contamination in an acute healthcare setting during the first and second pandemic waves. (February 2023) - Otter, J.A.; Zhou, J.; Price, J.R.; Reeves, L.; Zhu, N.; Randell, P.; Sriskandan, S.; Barclay, W.S.; Holmes, A.H.
Summary: Background: Surfaces and air in healthcare facilities can be contaminated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Previously, the authors identified SARS-CoV-2 RNA on surfaces and air in their hospital during the first wave of the coronavirus disease 2019 pandemic (April 2020). Aim: To explore whether the profile of SARS-CoV-2 surface and air contamination had changed between April 2020 and January 2021. Methods: This was a prospective, cross-sectional, observational study in a multi-site London hospital. In January 2021, surface and air samples were collected from comparable areas to those sampled in April 2020, comprising six clinical areas and a public area. SARS-CoV-2 was detected using reverse transcription polymerase chain reaction and viral culture. Sampling was also undertaken in two wards with natural ventilation alone. The ability of the prevalent variants at the time of the study to survive on dry surfaces was evaluated. Findings: No viable virus was recovered from surfaces or air. Five percent ( N =14) of 270 surface samples and 4% ( N =1) of 27 air samples were positive for SARS-CoV-2, which was significantly lower than in April 2020 [52% ( N =114) of 218 surface samples and 48% ( N =13) of 27 air samples ( P <0.001, Fisher's exact test)]. There was no clear difference in the proportion of surface and air samples positive for SARS-CoV-2 RNA based on the type of ventilation in the ward. All variants tested survived on dry surfaces for >72 h, with a <3-log10 reduction in viable count. Conclusion: This study suggests that enhanced infection prevention measures have reduced the burden of SARS-CoV-2 RNA on surfaces and air in healthcare facilities.